In-Situ Synthesis of AgNPs using Boesenbergia Rotunda L. Extract as Reducing Agent Development of Antibacterial and UV Protective Muslin Fabrics - Pimsin, Nipaporn; Janshongsawang, Jirapad; Chanthai , Saksit; Thongsom, Montakarn; Nuengmatcha, Prawit; Porrawatkul, Paweena (Trends in Sciences, 2025)
Muslin fabrics functionalized with silver nanoparticles (AgNPs) need to be produced via green synthesis to protect against ultraviolet (UV) radiation and antibacterial activity. In this study, we performed the green synthesis of AgNPs functionalized with fingerroot (Boesenbergia rotunda (L.) Mansf.) extract. The main bioactive component of fingerroot was investigated via GC-MS. The primary ingredient in fingerroot, pinostrobin, was shown to be the most prevalent, based on the GC-MS data. An eco-friendly approach involves obtaining such textile materials by AgNP synthesis directly (in situ) on muslin fabrics. The chemical linkages of colloidal AgNPs to the cellulosic structure were characterized and confirmed by FTIR, SEM, and EDX analyses. Compared to uncoated muslin fabric, AgNP-coated fabric provides excellent protection, with a UV protection factor (UPF) value of 43.30 and Insufficient protection, with a UPF value of 6.42. The antibacterial activity of AgNP-coated fabric was investigated, revealing greater inhibitory effects against Staphylococcus aureus (gram-positive) and Escherichia coli (gram-negative) microbial strains. A wash durability test was also performed on the treated fabric, and the findings showed that it could maintain strong antibacterial activity for up to 10 wash cycles. All of these findings pointed to the AgNPs produced in this study as a potentially useful ingredient for creating fabrics with strong antibacterial and UV protection properties. HIGHLIGHTS Green synthesis of silver nanoparticles (AgNPs) functionalized with fingerroot extract was performed, with pinostrobin identified as the primary bioactive component through GC-MS analysis. AgNP-coated muslin fabric exhibited excellent UV protection (UPF 43.30) and effective antibacterial activity against Staphylococcus aureus and Escherichia coli microbial strains. The AgNP coating demonstrated durability, retaining superior bacterial inhibitory activity even and UV protection ability after 10 wash cycles. Highlighting its promising material for preparing textiles with good antibacterial activity and UV protection. GRAPHICAL ABSTRACT